(untitled) (Bangladesh Journal of Medical Education, 2023)
Undergraduate pharmacology education has always been a topic of intense excitement and debate. This descriptive cross-sectional study was conducted to analyze the pharmacology written question papers (SAQ) of MBBS curriculum in last 10 years (January 2010 to November 2019). Total 131 question papers were collected, and reflection of curricular objectives and content coverage of pharmacotherapy of diseases of high burden were evaluated. Objective regarding factual knowledge (pharmacological effects, mechanisms of action, pharmacokinetic characteristics and adverse reactions of drugs) occupied about 80 percent of the questions throughout the last decade. Medicines used in diseases of high burden received very little weightage, which is consistent throughout the decade. Bangladesh Journal of Medical Education Vol.14(1) January 2023: 43-49